7 - Mothers in the Informal Economy and Changes in Child Feeding and Caring Roles in Kampala, Uganda: DOI: 10.4314/ad.v29i3.22203 - Ntozi, James (Africa Development, 2004)
The paper examines the child feeding and caring practices of mothers in an informal economy in Kampala City, using qualitative data collected in 1996. It was found that the supplementary feeding of children in this context started as early as three weeks despite the widespread belief among mothers that full breast feeding should go on up to at least three months. This action was justified in tenus of insufficient milk, working away from home, maternal illness, increased appetite of the child, sex of the child, child illness and contraception. This discussion, therefore, explores the ways in which, due to financial constraints, relatives as childcare providers are nonually relied on heavily by working mothers.